Drivers for enhancing job performance of prison officers in Slovenia: effects of job attitudes, organizational, and work-related factors - Podgorski, Katrin; Lobnikar, Branko; Mihelič, Anže; Prislan Mihelič, Kaja (Frontiers in Psychology, 2023)
Maintaining order and safety in a prison environment heavily depends on prison officers, who daily interact with prisoners and are constantly dealing with dangerous situations. Their task performance is vital for the organizational performance and the fulfilment of the prisons' mission. For managing prison officers' job performance efficiently, it is important to understand the associated factors; however, job performance in a prison environment remains completely unexplored in Slovenia. This article presents a study conducted among Slovenian prison officers (n = 201), which examined their task performance, its association with job attitudes, and the role of organizational and work-related factors. The study results showed that the prison officers' task performance is associated with their job satisfaction, but not with their job involvement. Moreover, their job satisfaction is associated with perceived organizational justice, job stress, and the dangerousness of the job. Based on these findings, we demonstrated that task performance depends on several direct and indirect factors that prison management should prioritize, the key ones being stress reduction, strengthening the feeling of organizational justice, and the ability to deal with the job-related dangers successfully. This article highlights organizational and work-related factors important for improving the prison officers' wellbeing at work.